1997
DOI: 10.1161/01.atv.17.8.1517
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Inflammatory Cell Adhesion Molecules Protects Against Atherosclerosis in Mice

Abstract: Leukocyte and endothelial cell adhesion molecules (CAMs) are essential for emigration of leukocytes, with the selectins mediating the initial step of leukocyte "rolling" and the beta 2-(CD18) integrins and intercellular adhesion molecule-1 (ICAM-1) being important for firm adhesion and emigration. On the basis of evidence for an inflammatory component in the pathogenesis of atherosclerosis, including increased expression of CAMs, cytokines, and growth factors, we tested the hypothesis that decreased expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
174
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(184 citation statements)
references
References 27 publications
5
174
0
2
Order By: Relevance
“…Deficiency of ICAM-1 expression in C57BL6 fat-fed animals showed a 75% protection against atherosclerosis when compared with wild-type animals. 23 However, one should note that ApoE-deficient animals fed a fat diet probably show lesions that are closer, compared with C57BL6, to those seen in human. Our data support a role for ICAM-1 at all stages of atherosclerosis in chow-fed animals.…”
Section: Bourdillon Et Al Vascular Lesions In Apoe/icam-1-deficient Micementioning
confidence: 98%
See 2 more Smart Citations
“…Deficiency of ICAM-1 expression in C57BL6 fat-fed animals showed a 75% protection against atherosclerosis when compared with wild-type animals. 23 However, one should note that ApoE-deficient animals fed a fat diet probably show lesions that are closer, compared with C57BL6, to those seen in human. Our data support a role for ICAM-1 at all stages of atherosclerosis in chow-fed animals.…”
Section: Bourdillon Et Al Vascular Lesions In Apoe/icam-1-deficient Micementioning
confidence: 98%
“…Morphometric analyses of intima lesion area over media area were carried out on the whole circumference of the proximal aortic arch, with the use of a previously described quantification method. 14,23,30 The number of sections used per animal was at least 5 per animal and per time point. Measurements were performed on ORO-stained slides for the different weeks of feeding (5 mice per group).…”
Section: Quantimetrymentioning
confidence: 99%
See 1 more Smart Citation
“…Although VCAM-1 knockout mice were unavailable, other adhesion molecule-deficient mice have been tested successfully in various models of atherosclerosis. Working with a C57BL/6 mouse model fed a high-cholesterol diet containing cholate, Nageh et al (12) showed that aortic lesion size is significantly reduced in ICAM-1 or P-selectin null mice or in mice with a hypomorphic mutation in the gene encoding the common CD18 subunit of β 2 integrins. In the more realistic apoE knockout model of atherosclerosis, in which mice have cholesterol levels between 500 and 2,000 mg/dl, depending on the diet offered, animals lacking P-selectin or ICAM-1 show significantly smaller aortic lesions (13,14).…”
mentioning
confidence: 99%
“…[7][8][9] Furthermore, mice deficient in VCAM-1 are protected against the development of atherosclerosis, 10 whereas the data regarding ICAM-1 knockout mice are conflicting. [10][11][12][13] Cell-bound adhesion receptors are relatively inaccessible in vivo. Fortuitously, soluble forms of VCAM-1 and ICAM-1 are found within the circulation.…”
mentioning
confidence: 99%